African American Male Students and the Achievement Gap: Building a Successful - Butler, S. Kent (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
This article explores the systemic inequalities found within educational systems that have long hampered educational achievements within the African American community, especially oppressions that continue to hinder the accomplishments made by young African American males. The achievement gap along with the history and culture of oppression are examined in relation to social supports and feelings of belonging to provide professional school counselors with effective interventions and strategies to utilize when serving this population.